Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Baamboozle terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di Kelas XI SMA Negeri 2 Padang Panjang - Salsabiela, Fadhilla; Marta, Rizkayeni; Jasril, Ilmiyati Rahmy; Zaus, Mahesi Agni (TSAQOFAH, 2025)
The issue of low student learning outcomes, particularly in Informatics subjects, remains a challenge in school-based learning processes. One potential solution is the use of instructional models that enhance student engagement, understanding, and motivation. This study aims to examine the effect of implementing the Problem Based Learning (PBL) model assisted by Baamboozle on students’ learning outcomes in Informatics at Grade XI of SMA Negeri 2 Padang Panjang. A quantitative method with a quasi-experimental design, specifically the Nonequivalent Control Group Design, was employed. The study population included all Grade XI students, with a sample of 72 students divided equally into an experimental class (36 students) and a control class (36 students). Data were collected through learning outcome tests and statistically analyzed. The results showed that the average post-test scores of the experimental class were higher than those of the control class. Data analysis confirmed a significant effect of the PBL model assisted by Baamboozle on the improvement of Informatics learning outcomes. These findings suggest that combining problem-based learning with educational game media such as Baamboozle can create a more engaging and interactive learning environment, positively impacting students’ academic achievement.